2023
DOI: 10.1002/sstr.202200275
|View full text |Cite
|
Sign up to set email alerts
|

Nano Organic Co‐Crystal Scintillator for X‐ray Imaging

Abstract: Traditional‐metal‐containing scintillators are widely used in X‐ray imaging due to their efficient X‐ray absorption and output of visible light. However, they suffer from heavy‐metal toxicity, environmental stability, harsh preparation, and afterglow. Metal‐free organic scintillators show a rising momentum, especially organic‐halogen‐containing molecules. Halogens are introduced to improve their X‐ray absorption, but the resulting increase in spin–orbit coupling leads to significant delayed fluorescence or pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Meanwhile, charge transfer between the donor and acceptor may potentially enhance the carrier transport efficiency of the material, thereby improving its scintillation performance. 20,21 Recently, Sun et al 22,23 demonstrated the feasibility of this strategy through their report on the organic co-crystal BIC scintillator.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, charge transfer between the donor and acceptor may potentially enhance the carrier transport efficiency of the material, thereby improving its scintillation performance. 20,21 Recently, Sun et al 22,23 demonstrated the feasibility of this strategy through their report on the organic co-crystal BIC scintillator.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table S1 and Figure d,e, a unit cell of both Cu-1 and Cu-2 single crystals consists of two Cu­(I) coordination molecules and two acetonitrile molecules, with each pair of molecules exhibiting two I···H–C interactions at distances of 3.888 Å (Cu-1) and 3.857 Å (Cu-2), respectively. The shorter I···H–C interactions in Cu-2 may restrict molecular vibration, thereby constraining nonradiative transition pathways. , Furthermore, we employed CrystalExplorer software to analyze the Hirshfeld surfaces and the distribution of different intermolecular interactions by generating two-dimensional fingerprint plots of these crystals. , As illustrated in Figure S4 and the pie charts in Figure h,i, compared with Cu-1, which has contributions from H···others interactions (73.1%), C···others interactions (18.5%), and I···others interactions (3.9%), the replacement of PH-Br in Cu-2 results in a more diverse array of intermolecular interactions, including H···others interactions (77.3%), C···others interactions (18.8%), I···others interactions (3.5%), and Br···others (4.9%). These plentiful intermolecular interactions effectively constrain molecular vibration and rotation, consequently further suppressing the nonradiative transition process. , Also, it is further supported by the calculated nonradiative transition rates ( k nr ), where the k nr values decreased from 6.61 × 10 4 s –1 in Cu-1 to 5.60 × 10 4 s –1 in Cu-2, leading to a significant enhancement of the RL intensity for Cu-2 in the solid-state. ,,, …”
Section: Resultsmentioning
confidence: 99%
“…X-ray detection technologies play a crucial role in various applications, including medical imaging, nondestructive testing, and security inspection. Scintillation X-ray detectors are widely utilized, and scintillators are essential components of these detectors. Traditional scintillators like CsI:TI OS:Tb, NaI:TI, and LYSO:Ce are commercially available. However, these scintillators face challenges, such as a complex preparation process, high cost, light scattering, long afterglow, and poor stability, limiting their widespread application. Moreover, the incorporation of toxic elements like TI in high-performance scintillators poses significant safety risks . Therefore, there is an immediate need to investigate advanced scintillator materials with high performance.…”
Section: Introductionmentioning
confidence: 99%